Fiscal Policy for Mitigating the Social Impact of High Energy and Food Prices - Amaglobeli, David (International Monetary Fund, 2022)
Fiscal policy has a crucial role in lessening the impact on the most vulnerable households. Governments must balance by ensuring access to energy and food, normalizing fiscal policy after unprecedented support in 2020, and promoting green transformation.